Correlation properties of heart rate variability to assess the first ventilatory threshold and fatigue in runners - Van Hooren, B.; Mennen, B.; Gronwald, T.; Bongers, B. C.; Rogers, B. (Journal of Sports Sciences, 2025)
Purpose The short-term scaling exponent alpha1 of detrended fluctuation analysis (DFA-a1) of heart rate variability (HRV) has shown potential to delineate the first ventilatory threshold (VT1). The aims of this study were to investigate the accuracy of this method for VT1 determination in runners using a consumer grade chest belt and to explore the effects of acute fatigue.